Brainlesion : glioma, multiple sclerosis, stroke and traumatic brain injuries : first International Workshop, Brainles 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015, Revised selected papers /: glioma, multiple sclerosis, stroke and traumatic brain injuries : first International Workshop, Brainles 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015, Revised selected papers. (2016) - Unknown
No abstract available